Towards a complete knowledge of the bryophyte flora from Serra dos Carajás, eastern Amazonia, based on new and old collections - Silva, Jainara P.; Oliveira-Da-Silva, Fúvio R.; Takashima, Tássia T.g; Ilkiu-Borges, Anna L. (Phytotaxa, 2025)
This study presents a more comprehensive understanding of bryophyte flora recorded in the Serra dos Carajás, eastern Amazonia. We provide a list of species based on new and past records, as well as data on world geographic distribution, environment distribution in Carajás, and substrate preference. One hundred and eighty-three (183) species, 12 varieties and one subspecies of bryophytes were identified for the Serra dos Carajás, distributed across 87 genera and 32 families. The richness of mosses was slightly higher (54%) than liverworts (46%), an unusual result in floristic studies of bryophytes in Amazonia. The list of species for Carajás is expanded by 50 species and two varieties of bryophytes (mainly liverworts), including Prionolejeunea decora as a new record for Brazil. Most species have a neotropical distribution and a few are endemic to Brazil. Corticolous species prevailed over other guilds, and liverworts showed a specialized substrate colonization pattern compared to mosses. Although the forested environments are still under-collected, the Serra dos Carajás is the second area with the largest number of bryophytes species in eastern Amazonia, after Caxiuanã National Forest.